Scapulohumeral kinematic assessment of the forward kayak stroke in experienced whitewater kayakers - Wassinger, C. A.; Myers, J. B.; Sell, T. C.; Oyama, S.; Rubenstein, E. N.; Lephart, S. M. (Sports Biomechanics, 2011)
By understanding the normal humeral and scapular kinematics during the kayak stroke, inferences about the relationship of kayaking technique and shoulder injury may be established. The purpose of this study was to describe scapular and humeral kinematics and to compare dominant versus non-dominant symmetry in healthy whitewater kayakers performing the forward stroke. Twenty-five competent whitewater kayakers (mean age: 34.1 ± 9.4 years, mean height: 1.768 ± 0.093 m, mean mass: 78.2 ± 13.0 kg) underwent humeral and scapular kinematic assessment, using an electromagnetic tracking device, while kayaking on a kayak ergometer. Paired t-tests were used to determine symmetry. Scapular and humeral kinematic means and standard deviations at six time points during the kayak stroke were described. Scapular and humeral kinematics were shown to be similar upon bilateral comparison. The greatest potential for injury during the forward stroke may be at thrust paddle shaft vertical when the humerus is maximally elevated in internal rotation and adduction as subacromial structures may be mechanically impinged. The relationship between scapulohumeral kinematics related to injury at other time points are also described.